INVERSE MONTE CARLO SIMULATION OF THE LITHOSPHERIC THERMAL REGIME IN THE FENNOSCANDIAN SHIELD USING XENOLITH-DERIVED MANTLE TEMPERATURES - Jokinen J.; Kukkonen I.T. (My University, 2000)
Monte Carlo inversion was applied in 2-dimensional conductive steady-state thermal simulation of a 600-km long lithosphere transect in the Fennoscandian Shield. The thermal regime in the mantle was constrained with thermobarometric data derived from kimberlite-hosted mantle xenoliths in eastern Finland, which suggest an average temperature of 1250±50°C at 208 km, but no partial melting down to at least 240 km. A priori models were generated from probability distributions assigned to thermal conductivity and heat production rate values of the 38 domains in the model, as well as the mantle heat flow density used as the lower boundary condition in the simulations. The forward problem was solved with a finite difference code, and the modification of the a priori distributions into a posteriori distributions was done using the Metropolis algorithm as the acceptance rule. The two-stage inversion, first using the measured surface heat flow values as a fitting object, and second, re-sampling the obtained a posteriori models but using xenolith-derived mantle temperature data as a fitting object, results in a considerable improvement in the resolution and average values of temperature and heat flow density in the model. The improvement can be seen in the model results to a distance of about 400 km from the xenolith area. The obtained results support a scheme that mantle heat flow is low in the thickest lithosphere area of the Fennoscandian Shield and about 10±1 mW m−2 at 200 km, and 13±1 mW m−2 in the uppermost subcrustal mantle. The inversion results suggest that there is no partial melt-bearing asthenosphere under the transect at depths shallower than at least 250 km. The seismic lithosphere-asthenosphere boundary is at depths of 110–170 km on the transect and corresponds to about 1100°C temperature in our model. This transition can be related to a zone of rheological weakening but not to the onset of melting. The mantle temperature and heat flow value in the eastern Finland kimberlite province are in agreement with models where small-scale convection (solid state creep) transports heat to the base of the lithosphere at about 250 km depth.